Fragmentation and Integration in Educational Research: A Systematic Review of Self-Efficacy, Character, and Green Education - Shanta Rezkita; Ahmad Umam Mustopa; Primus Devra Raihan (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the fragmentation of research on self-efficacy, character building, and green education, which are often examined separately despite their potential interconnection in shaping holistic learners. The objective of this study is to synthesize how self-efficacy and character education are positioned within the framework of green education and to identify their integrative potential. A systematic literature review was conducted using the PRISMA 2020 protocol with Scopus as the primary database. Two keyword strategies were applied, yielding 174 records, of which 33 peer-reviewed Q1–Q3 articles met the inclusion criteria. Data were analyzed using thematic synthesis based on research focus, methodology, educational level, and main findings. The results reveal three dominant but fragmented clusters: self-efficacy as a psychological construct for academic confidence, character education as moral and social development, and green education as curricular and institutional innovation. The synthesis further shows that green education provides a promising context for integrating self-efficacy and character through sustainability-based learning experiences. In conclusion, this study proposes an integrative framework in which psychological confidence, moral formation, and ecological awareness interact to support transformative education in primary and secondary schools.